2018
DOI: 10.1002/rth2.12093
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3, single‐arm, multicenter study of dabigatran etexilate for secondary prevention of venous thromboembolism in children: Rationale and design

Abstract: BackgroundAnticoagulant therapy for venous thromboembolism (VTE) in children is largely based on treatment recommendations for adults. However, differences in both physiology (ie, renal maturation and drug excretion) and developmental hemostasis must be considered when treating children, as such differences could affect dose appropriateness, safety and efficacy.ObjectivesTo address these concerns, a study was designed to evaluate the safety of dabigatran etexilate in children requiring secondary thrombus preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The trial design has been described in detail previously. 18 In brief, this open-label, single-arm, safety prospective cohort, phase 3 clinical trial (NCT02197416) (supplemental Figure 1, available on the Blood Web site) is a part of a Pediatric Investigational Plan agreed upon with the EMA Pediatric Committee, and a postmarketing requirement agreed upon with the US FDA. The main objective was to assess the safety of dabigatran etexilate for secondary prevention of VTE; all study outcomes were considered safety related.…”
Section: Trial Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial design has been described in detail previously. 18 In brief, this open-label, single-arm, safety prospective cohort, phase 3 clinical trial (NCT02197416) (supplemental Figure 1, available on the Blood Web site) is a part of a Pediatric Investigational Plan agreed upon with the EMA Pediatric Committee, and a postmarketing requirement agreed upon with the US FDA. The main objective was to assess the safety of dabigatran etexilate for secondary prevention of VTE; all study outcomes were considered safety related.…”
Section: Trial Designmentioning
confidence: 99%
“…The main objective was to assess the safety of dabigatran etexilate for secondary prevention of VTE; all study outcomes were considered safety related. The current analysis includes the data set and target enrollment 18 that fulfills the requirements of the European Union (EU) Pediatric Investigational Plan agreed with the EMA Pediatric Committee, while recruitment continued in order to fulfill additional US FDA requirements. The trial was conducted in accordance with the Declaration of Helsinki and the principles of Good Clinical Practice, and was approved by all investigational site ethics committees.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…75 In addition, an interim analysis of a single-arm, prospective cohort, phase III study demonstrated a favorable safety profile of dabigatran used for up to 12 months in approximately 200 children aged 0 to <18 years who required anticoagulation for the secondary prevention of VTE and with a persistent risk factor for VTE. 76,77 The phase III EINSTEIN Junior trial evaluated rivaroxaban (20 mg o.d. equivalent adjusted according to body weight following at least 5 days of initial heparin therapy) versus standard of care anticoagulation therapy for the treatment of acute VTE in approximately 500 children and neonates.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…8 Anticoagulant choices currently include oral vitamin K antagonists or agents (broadly abbreviated as VKA herein), subcutaneously injected low molecular weight heparin (LMWH), and with an expanding market share for the newer direct oral anticoagulants (DOACs). [9][10][11] Treatment regimens differ by dose interval, delivery route, and/or necessity for therapeutic monitoring.…”
Section: Introductionmentioning
confidence: 99%